Peran Pendidikan Agama Islam dalam Pembentukan Karakter Religius Peserta Didik di MTS Al-Jamaiyyah Medan Denai - Nurhalimah Lubis; Sintya Utari; ifronsiregar@gmail.com; Zainal Abidin (Lembaga Pengembangan Kinerja Dosen, 2026)
This study discusses the role of Islamic Religious Education in the formation of religious character of students at MTs Al-Jamaiyyah Medan Denai. Islamic Religious Education has an important function in instilling the values of faith, piety, and noble morals in students. In the era of globalization and increasingly rapid technological development, students face various moral challenges that can influence their behavior and character. Therefore, the formation of religious character is one of the main objectives in the educational process. This study used a qualitative method with data collection techniques through observation, interviews, and documentation. The results show that Islamic Religious Education plays an important role in forming the religious character of students through the learning process, habituation of religious activities, and teacher role models. Religious activities such as congregational prayer, reading the Qur'an, and socio-religious activities can help students apply Islamic values in everyday life. In addition, the success of religious character formation is also influenced by cooperation between the school, family, and the community environment. In this way, Islamic Religious Education is expected to be able to form a generation that is faithful, devout, has noble character, and is able to face the challenges of contemporary developments while adhering to Islamic values.